Effect of Religiusity, Locus of Control, and Professional Commitment to Whistleblowing Intention - Aida Fitri, Fauziah; Indayani, Indayani; Tursina, Ade (Opción, 2019)
In this research study , we apply theory of behavioral to intent auditor whistle- blowing. The purpose of this paper is to examine the effect of religiosity, locus of control, and professional commitment on whistleblowing intention. The data was collected by using questionnaire and sent to auditors intern who worked at inspec- torate of Aceh province government. The samples are chosen using simple random sampling method and resulted 41respondents. This research uses the multiple lin- ear regression analysis to test the hypothesis.The findings of this studyindicates that religiosity, locus of control, and professional commitment have the effect on whistleblowing intention.